Consumer Demand for Fair Trade: Evidence from a Multistore Field Experiment - Hainmueller, Jens; Hiscox, Michael J.; Sequeira, Sandra (The Review of Economics and Statistics, 2015)
We provide new evidence on consumer demand for ethical products from experiments conducted in a U.S. grocery store chain. We find that sales of the two most popular coffees rose by almost 10% when they carried a Fair Trade label as compared to a generic placebo label. Demand for the higher-priced coffee remained steady when its price was raised by 8%, but demand for the lower-priced coffee was elastic: a 9% price increase led to a 30% decline in sales. While consumers attach value to ethical sourcing, there is significant heterogeneity in willingness to pay for it.